Acting like a physicist: Student approach study to experimental design - Anna Karelina (American Physical Society, 2007)
National studies of science education have unanimously concluded that preparing our students for the demands of the 21st century workplace is one of the major goals. This paper describes a study of student activities in introductory college physics labs, which were designed to help students acquire abilities that are valuable in the workplace. In these labs [called Investigative Science Learning Environment (ISLE) labs], students design their own experiments. Our previous studies have shown that students in these labs acquire scientific abilities such as the ability to design an experiment to solve a problem, the ability to collect and analyze data, the ability to evaluate assumptions and uncertainties, and the ability to communicate. These studies mostly concentrated on analyzing students’ writing, evaluated by specially designed scientific ability rubrics. Recently, we started to study whether the ISLE labs make students not only write like scientists but also engage in discussions and act like scientists while doing the labs. For example, do students plan an experiment, validate assumptions, evaluate results, and revise the experiment if necessary? A brief report of some of our findings that came from monitoring students’ activity during ISLE and nondesign labs was presented in the Physics Education Research Conference Proceedings. We found differences in student behavior and discussions that indicated that ISLE labs do in fact encourage a scientistlike approach to experimental design and promote high-quality discussions. This paper presents a full description of the study.